2022
DOI: 10.3389/ijph.2022.1605064
|View full text |Cite
|
Sign up to set email alerts
|

System Dynamic Model Simulates the Growth Trend of Diabetes Mellitus in Chinese Population: Implications for Future Urban Public Health Governance

Abstract: Objectives: To simulate the growth trend of diabetes mellitus in Chinese population.Methods: The system dynamic modeling methodology was used to establish a population prediction model of diabetes with or without cardiovascular diseases. Lifestyle therapy and the use of metformin, acarbose, and voglibose were assumed to be intervention strategy. The outcomes will be examined at 5, 15, and 30 years after 2020.Results: The projected number of diabetic population in China would increase rapidly from 141.65 millio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…NPTN-IT1 is a recently identified lncRNA, located on chromosome 15q24.1, which has a low expression level in tumor tissues and can inhibit the growth and metastasis of hepatocellular carcinoma, lung adenocarcinoma (Yang et al, 2013;Liu et al, 2016), nasopharyngeal carcinoma and cervical cancer (Jiang et al, 2015;Sun et al, 2015). LINC02362 is associated with better prognosis of HCC patients, and inhibits the survival, migration and invasion of HCC cells and epithelial interstitial transformation (EMT) (Li et al, 2022b). Although there is no relevant study on the above lncRNANs in diabetes, it is well known that hypoxia is an important feature of tumor microenvironment, and the above lncRNAN regulates tumor growth through hypoxia related pathways, and may also affect glucose metabolism through hypoxia related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…NPTN-IT1 is a recently identified lncRNA, located on chromosome 15q24.1, which has a low expression level in tumor tissues and can inhibit the growth and metastasis of hepatocellular carcinoma, lung adenocarcinoma (Yang et al, 2013;Liu et al, 2016), nasopharyngeal carcinoma and cervical cancer (Jiang et al, 2015;Sun et al, 2015). LINC02362 is associated with better prognosis of HCC patients, and inhibits the survival, migration and invasion of HCC cells and epithelial interstitial transformation (EMT) (Li et al, 2022b). Although there is no relevant study on the above lncRNANs in diabetes, it is well known that hypoxia is an important feature of tumor microenvironment, and the above lncRNAN regulates tumor growth through hypoxia related pathways, and may also affect glucose metabolism through hypoxia related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing appropriate interventions has the potential to effectively delay this progression. [6] Sodium glucose cotransporter type 2 (SGLT2) inhibitors represent a new class of antidiabetic medications for the treatment of diabetes, and act inhibits renal glucose reabsorption, thereby increasing urinary glucose excretion and lowering the glucose burden on the organism. [7][8][9] Since SGLT2 inhibitors have been extensively studied and demonstrated to significantly reduce cardiovascular events such as HF and myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the diabetes prevalence among Chinese adults has already exceeded 10%, and it is still on the rise, with an estimated increase to 202.84 million patients by 2050. [4] Existing treatment methods mainly include medication, laser therapy, and surgical intervention. However, these treatments have their limitations.…”
Section: Introductionmentioning
confidence: 99%